Fiscal Multipliers over the Growth Cycle : Evidence from Malaysia - Rafiq, Sohrab (2012)
This paper explores the stabilisation properties of fiscal policy in Malaysia using a model incorporating nonlinearities into the dynamic relationship between fiscal policy and real economic activity over the growth cycle. The paper also investigates how output multipliers for government purchases may alter for different components of government spending. The authors find that fiscal policy in Malaysia has become increasingly pro-cyclical over the last 25 years and establish that the size of fiscal multipliers tend to change over the growth cycle. A 1 Malaysian Ringgit rise in government (investment) spending leads to a maximum output multiplier of around 2.7 during growth recessions, and around 2 in normal times. The returns to government spending in Malaysia are greater when the focus is on public investment, as opposed to consumption. Changes in tax policy are less effective in stimulating economic activity than direct government spending. These results provide empirical backing to conjectures in the recent literature implying that procyclicality in fiscal policy reduces the effectiveness of fiscal actions in emerging markets.